دعوت ِدین کی معنویت و افادیت: اردو تفسیری ادب کا مطالعہ: Usefulness of Da'wah: A Study of Urdu Commentaries of the Quran (Al-Qamar, 2021)
Da'wah includes everything that is meant to promote and spread goodness. The principles of Da'wah are the words of Qur'an and Hadith. Therefore, the spreading the message of Qur'an and Hadith is also Da'wah. This article gives the details with examples which have the status of the best guidance in view of the requirements of every age. Appreciating the virtues in the religion increases the prestige of the religion of Islam that it is the religion that makes our world good. And of course, it will bring the best success in the hereafter as well. The da'wah of religion shows beauty in the systems of life due to which human society looks beautiful and popular and the peace and stability of the society is prominent. There are treasures of details commentaries of the Quran which this paper explores.
Keywords: Quran; dawah; Principle; Urdu Tafsir